Pemetaan bibliometrik terhadap perkembangan penelitian arsitektur informasi pada Google Scholar menggunakan VOSviewer - Fina Nurul Zakiyyah; Yunus Winoto; Rohanda Rohanda (Jurnal Informatio, 2022)
Information architecture is a process of organizing information that can make it easy for users to meet their information needs, provide current location instructions in an information link, and make it easier for users to maintain information in a large collection of information. Information architecture has an important role in designing a website, because in it there are processes of research, strategy, design, implementation, and administration that can play a role in structuring, organizing, and labeling. This study aims to determ (istilah)ine the development of research publications within 11 (eleven) years, tofind out the direction of information architecture research trends, to identify the relationship between scientific concepts, and to know the information architecture science network based on keywords (co- occurrence) and collaboration of authors (coauthorship). The method used in this research is descriptive bibliometric analysis, the data used is taken in the range of 2011 – 2021. Data collection is based on the Google scholar database with information architecture keywords and additional supporting keywords including website, design, wireframe, and labelling system with the number of publications is limited to 500 journals. Data was collected using Publish or Perish (PoP) software asmetadata. Data analysis was performed using Vosviewer software as a medium for bibliometric analysis. The results show that in the last 11 years the number of publications on information architecture research indexed by Google scholar has fluctuated, but in term (istilah)s of quantity, it has increased significantly. The highest publication growth development occurred in 2020, reaching 60 journals (14.1%), while the lowest publication occurred in 2011 with a total of 12 journals (2.8%).Mapping the development of information architecture research publications based on co-authorship shows a correlation or relationship between researchers centred on Wing Wahyu Winarno. While the mapping of the development of information architecture research publications based on keywords (co- occurrence) indicates a relationship between one term (istilah) and another accompanied by 3 dominant clusters, although this research has not been widely studied, research in the field of information architecture can create opportunities for researchers.